Progress in Genome Editing Technology and Its Application in Plants - Zhang, Kai; Raboanatahiry, Nadia; Zhu, Bin; Li, Maoteng (Frontiers in Plant Science, 2017)
Genome editing technology (GET) is a versatile approach that has progressed rapidly as a mechanism to alter the genotype and phenotype of organisms. However, conventional genome modification using GET cannot satisfy current demand for high-efficiency and site-directed mutagenesis, retrofitting of artificial nucleases has developed into a new avenue within this field. Based on mechanisms to recognize target genes, newly-developed GETs can generally be subdivided into three cleavage systems, protein-dependent DNA cleavage systems (i.e., zinc-finger nucleases, ZFN, and transcription activator-like effector nucleases, TALEN), RNA-dependent DNA cleavage systems (i.e., clustered regularly interspaced short palindromic repeats-CRISPR associated proteins, CRISPR-Cas9, CRISPR-Cpf1, and CRISPR-C2c1), and RNA-dependent RNA cleavage systems (i.e., RNA interference, RNAi, and CRISPR-C2c2). All these techniques can lead to double-stranded (DSB) or single-stranded breaks (SSB), and result in either random mutations via non-homologous end-joining (NHEJ) or targeted mutation via homologous recombination (HR). Thus, site-directed mutagenesis can be induced via targeted gene knock-out, knock-in, or replacement to modify specific characteristics including morphology-modification, resistance-enhancement, and physiological mechanism-improvement along with plant growth and development. In this paper, an noncomprehensive review on the development of different GETs as applied to plants is presented.